PWE-078 Interactions with hepatitis c therapies – is the pharmacist now your best friend?. (17th June 2017) - Torkington, A; ,; Cripps, S; Lee, K; Pratt, A; Selby, P; Davidson, K; Spollen, S; Mahungu, J; Morgan, H; Boyle, A; Vaghjiani, T; et al.
Abstract : Introduction: Directly active antivirals (DAA's) are highly effective agents which are ensuring the cure of the majority of Hepatitis C (HCV) patients with all forms of severity of disease. High rates of co-morbidities and polypharmacy in this patient group means thorough drug-drug interaction (DDI) checks are essential. EASL Recommendations on Treatment of Hepatitis C 2016 recognises that numerous and complex DDI are possible with the use of DAAs. Therefore it is recommended that co-medicines are assessed for potential DDI prior to and during treatment. Clinical pharmacists are a key member of the multidisciplinary team to perform this task to ensure safe and effective treatment. We set out to evaluate the incidence of DDIs in the UK and its impact on treatment. Method: We performed a retrospective evaluation of HCV patients receiving hepatitis C therapy with DAAs seen across 17 UK centres from August 2015 until April 2016. Data were collected on demographics, HCV genotype (GT), choice of DAA and additional monitoring required. The Liverpool hep-druginteractions.org website was used to evaluate presence and severity of potential DDIs. Results: 975 patients were identified of which 684/975 (70%) were male and median 53 (23-89) years old. 608/975 (62%) were HCV GT 1, 50/975 (5%) were GT 2, 237/975 (24%) were GT 3, 65/975 (7%) were GT 4. 564/975 (58%) were cirrhotic. The HCV regimens chosen based on local policies are listed in table 1. 3808 co-medicines were identified in 804/975 (82%) of patients (median of 5.5 medicines/patient). Of the co-medications prescribed: 26% were CNS drugs, 19% cardiac drugs, 12% gastric drugs, 5% HIV drugs and 4.5% opioid substitution therapies. There were 702 interactions identified. Of these 678 (96%) were amber DDIs (close monitoring/dosage adjustment required), with 24 (4%) were red (do not co-administer). Conclusion: This study has shown that although polypharmacy is common in this cohort of patients, this does not preclude cost effective HCV treatment options. The expertise of the clinical pharmacist is essential to ensure accurate screening and advice on managing DDIs to ensure optimal treatment outcomes. Disclosure of Interest: None Declared